1969
DOI: 10.1111/j.1570-7458.1969.tb02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of Plant‐sucking Insects on Chemically Defined Diets

Abstract: With the advent of suitable techniques for rearing plant-sucking insects, especially aphids, on chemically defined diets, knowledge of their nutrition has evolved considerably over the past 7 years. Thus, contrary to some earlier beliefs, the nutritional requirements of plantsucking insects have been found to be, with minor exceptions, generally similar to those of other insects, and it is now possible to sustain aphid colonies on artificial diets for two or more generations, and in some cases, for an almost i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 65 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…The fact that, in previous experiments, sucrose was the most suitable carbohydrate substrate for aphid growth and propagation suggested that sucrose is an important cue for aphid orientation (Auclair, 1963;Auclair, 1969;Mittler and Dadd, 1964;Kimmins, 1982). Previous choice-chamber experiments (Mittler and Dadd, 1964) using M. persicae showed a distinct preference for sucrose solutions in comparison with amino acid or control solutions.…”
Section: Discussion the Quest For Orientation Cues By Use Of Aphid-admentioning
confidence: 96%
See 1 more Smart Citation
“…The fact that, in previous experiments, sucrose was the most suitable carbohydrate substrate for aphid growth and propagation suggested that sucrose is an important cue for aphid orientation (Auclair, 1963;Auclair, 1969;Mittler and Dadd, 1964;Kimmins, 1982). Previous choice-chamber experiments (Mittler and Dadd, 1964) using M. persicae showed a distinct preference for sucrose solutions in comparison with amino acid or control solutions.…”
Section: Discussion the Quest For Orientation Cues By Use Of Aphid-admentioning
confidence: 96%
“…According to a long-standing hypothesis (Auclair, 1969), aphids seem to employ information from punctured plant cells along the stylet pathway for sieve-tube recognition by sensing the high sugar content and slightly alkaline pH values characteristic of sieve-tube sap.…”
Section: Introductionmentioning
confidence: 99%
“…Auclair, 1963;Auclair, 1969;Mittler and Dadd, 1963;Simpson et al, 1995) have demonstrated that aphids perform best on diets that mimic the sucrose and pH composition of sieve-tube sap (pH values of approximately 7.0 and a high concentration of sucrose). A preference for similar diets in choice chambers (Mittler and Dadd, 1964;Hewer et al, 2010) indicates that aphids have the sensory means to identify sieve tubes in plant tissues (Hewer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar outcomes occur when nymphs develop on less-favored alternate host plants (Moran, 1968). In aphids amino acid concentrations are known to influence growth and reproduction (Auclair, 1969). It is very probable that the immature stages may have high demands for protein and that protein starvation contributed to the nymphal mortality.…”
Section: Comparative Life Cycle Of D Citrimentioning
confidence: 99%